Conductive slurry for base metal layer of stacked gate of BC battery and preparation method of conductive slurry
By using the conductive paste for the base metal layer of the BC cell cured low-temperature grid cured in photovoltaic technology, the problems of high temperature sintering and high silver content are solved, and low-cost and high-efficiency photovoltaic cell manufacturing is achieved, while avoiding the oxidation of base metals.
Patent Information
- Application Number
- CN202510189895.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing photovoltaic technology, high temperature sintering and high silver content lead to high costs, and in low temperature HJT technology, silver-copper contact is relatively large, and base metals are prone to oxidation, affecting conductive properties.
The conductive paste for the base metal layer of the BC cell cured by low temperature is composed of 92-93 wt% base metal powder, 3.8-4.2 wt% resin, 1.0-1.2 wt% curing agent, 1.2-2 wt% solvent, 0.3-0.8 wt% additive and 0.5-1 wt% antioxidant. The antioxidant is a mixture of benzotriazole, triethanolamine, copper cycloalkane acid salt, etc.
Rapid curing below 150-180 °C is achieved, ensuring good contact and vertical conduction of base metal conductive seed layer, reducing costs and improving efficiency, while avoiding the loss of conductive performance caused by oxidation.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery conductive paste, and in particular to a conductive paste for a BC battery stacked grid base metal layer and a preparation method thereof. Background Art
[0002] In the photovoltaic environment of reducing costs and increasing efficiency, the current market silver price is high. TOPCon technology has high silver content and high sintering temperature. The raw material cost and production cost are extremely high. HJT technology, the latest silver-copper technology, while reducing costs, inevitably loses the good contact conductivity of pure silver. Both technical routes are constantly reducing silver unit consumption and processing fees, which has a significant impact on the photovoltaic industry environment. It is worth noting that at present, in addition to the mainstream technology SMBB and the 0BB technology route that has recently attracted much attention from the industry, various manufacturers are competing fiercely for low cost and high efficiency; for the N-type TOPCon technology route, the slurry is a pure silver powder system, the slurry cost is high, and the future development direction is thinning, 0BB, etc.; for the heterojunction HJT technology route, the slurry changes from a pure silver formula to a silver-copper formula, and the future development direction is 0BB, electroplated copper, etc. In general, both technology routes are reducing the cost brought by the slurry. Summary of the invention
[0003] In order to solve the current problems, a technical solution of low-temperature solidification of silver conductive seed layer stacked gate and low-temperature solidification of base metal layer is proposed; firstly, it solves the cost problem of high-temperature TOPCon high silver content and high-temperature sintering; secondly, it solves the problem of large contact of the latest silver-copper technology of low-temperature HJT; thirdly, it solves the problem of easy oxidation of base metals such as copper paste.
[0004] The technical solution of the present invention is as follows: The first object of the present invention is to provide a conductive paste for a BC battery stacked grid base metal layer, the raw material composition is: (A) 92-93wt% base metal powder, (B) 3.8-4.2wt% resin, (C) 1.0-1.2wt% curing agent, (D) 1.2-2wt% solvent, (E) 0.3-0.8wt% additive, (F) 0.5-1wt% antioxidant; The antioxidant is a mixture of benzotriazole, triethanolamine, copper cyclohexaneate, a coupling agent and a dispersant.
[0005] In one embodiment of the present invention, the antioxidant is a mixture of benzotriazole, triethanolamine, copper cyclohexaneate, silane coupling agent KH560 and dispersant BYK-111 (phosphate ester).
[0006] In one embodiment of the present invention, the preparation method of the antioxidant is as follows: 20-25wt% of copper cyclohexaneate, 25-30wt% of triethanolamine, 15-25wt% of benzotriazole, 10-20wt% of silane coupling agent KH560 and 5-10wt% of dispersant BYK-111 (phosphate ester) are mixed, stirred, and three-roll milled twice to prepare the antioxidant.
[0007] The compounded antioxidant has a good antioxidant effect at about 200°C, which ensures the antioxidant properties of easily oxidizable base metal powders such as copper powder and avoids the loss of conductive properties caused by oxidation.
[0008] In one embodiment of the present invention, the base metal powder is one of copper powder, nickel powder, tin powder and aluminum powder, or a mixture of two of them.
[0009] In one embodiment of the present invention, the copper powder is a mixture of micron-sized copper powder and nano-sized copper powder.
[0010] In one embodiment of the present invention, the nickel powder is a mixture of micron-sized nickel powder and nano-sized nickel powder.
[0011] In one embodiment of the present invention, the average particle size D50 of the micron-sized copper powder is 3.0-4.0 μm, and the tap density is 3-5 g / cm 3 , which can be spherical or spherical.
[0012] When the micron-scale copper powder is spherical in shape, the preferred particle size is about 3.5 μm. When the particle size is greater than 4 μm, the gap between the conductive powder and the sintered conductive layer cannot be tightly filled, which increases the contact resistance. Since the contact surface is the sintered conductive layer, not the pyramid velvet surface of the battery cell, the surface of the conductive layer will be relatively flat. When the particle size is less than 3 μm, the number of contact points between the powder particles will decrease. Because in a certain volume of powder, a small particle size means an increase in the number of particles, but the contact method between the particles becomes more "point contact", and the line resistance will increase.
[0013] In one embodiment of the present invention, the average particle size D50 of the nano-copper powder is 80-300 nm, and the tap density is 5.5-6.8 g / cm 3 , which is spherical or spherical.
[0014] In one embodiment of the present invention, the average particle size D50 of the micron-sized nickel powder is 3.0-4.0 μm, and the tap density is 3-5 g / cm 3 , which is spherical or spherical.
[0015] In one embodiment of the present invention, the average particle size D50 of the nano-sized nickel powder is 120-200 nm, and the tap density is 5.5-6.8 g / cm3 , which is spherical or spherical.
[0016] The use of base metal powders significantly reduces silver consumption, thereby reducing non-silicon costs in solar cells.
[0017] In one embodiment of the present invention, the resin is one or more of epoxy resin, polyester resin, polyurethane resin, chloroacetic acid resin, phenoxy resin, polyimide resin, and acrylic resin.
[0018] In one embodiment of the present invention, in order to achieve good conductivity, an epoxy resin with good adhesion can be selected, and a polyester resin with good flexibility and weather resistance, a polyurethane resin and an acrylic resin, a chloroacetic resin, and a phenoxy resin that provide good shrinkage and weather resistance can be matched.
[0019] In one embodiment of the present invention, the epoxy resin is a bisphenol A epoxy resin or a bisphenol F epoxy resin, but is not limited thereto.
[0020] In one embodiment of the present invention, the molecular weight of the acrylic resin is 45,000-55,000, but is not limited thereto.
[0021] In one embodiment of the present invention, the hydroxyl value of the polyester resin is 20-30, but is not limited thereto.
[0022] In one embodiment of the present invention, the molecular weight of the phenoxy resin is 30,000-40,000, but is not limited thereto.
[0023] In one embodiment of the present invention, the curing agent is one or more of blocked hexamethylene diisocyanate trimer, phthalic anhydride, methyltetrahydrophthalic anhydride, and 2-methylimidazole.
[0024] In one embodiment of the present invention, the curing agent is blocked hexamethylene diisocyanate trimer, the deblocking temperature is 130° C., and the blocking agent is DEM (diethylene glycol monomethyl ether).
[0025] In one embodiment of the present invention, the solvent is one or more of DBE (dibasic acid ester), alcohol ester dodecanedioate, dimethyl adipate, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, N-methylpyrrolidone, 1,6-hexanediol diglycidyl ether, trimethylolpropane trimethacrylate, and glycerol.
[0026] In one embodiment of the present invention, the auxiliary agent is one or more of a dispersant, a coupling agent, a hydroxy silicone oil, and a curing accelerator.
[0027] In one embodiment of the present invention, the dispersant is one or more of oleic acid, polyethylene glycol, and isooctyl polyoxyethylene ether phosphate; the coupling agent is one or more of KH550, KH560, and KH570; and the curing accelerator is one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, boron trifluoride complex, dicyandiamide, and organic urea.
[0028] The second object of the present invention is to provide a method for preparing the above conductive paste, comprising the following steps: Add the required resin, curing agent, solvent, additive and antioxidant in proportion, stir evenly by hand, add base metal powder, stir manually until it is moist and free of dry powder, then grind with three rollers, with the gap from large to small, and the minimum gap must not be less than 10μm; grind 6 times, can; put into a rotary mixer, stir at 800-1000 rpm for 1-2 min, and the preparation is complete.
[0029] The third object of the present invention is to provide a BC battery stack containing the above-mentioned conductive paste, wherein the BC battery stack structure is divided into two layers, the lower layer is a conductive seed layer formed by HJT silver-copper paste, and the upper layer is a base metal layer containing the above-mentioned conductive paste.
[0030] In one embodiment of the present invention, the silver content of the lower HJT silver copper paste is controlled at 25-30wt%; the paste of the conductive seed layer accounts for 10-20wt% of the entire grid line; the silver content of the upper conductive paste is 0%, and the paste accounts for 80-90wt% of the entire grid line; The upper and lower layers are cured at low temperature; the temperature is controlled at 150-180 ℃.
[0031] The beneficial technical effects of the present invention are: The conductive paste of the present invention can achieve rapid solidification below 150-180° C., can achieve good contact with the base metal conductive seed layer, provide good vertical conduction, and achieve good efficiency gain and cost reduction.
[0032] The antioxidant of the present invention can make the slurry have good oxidation resistance, ensure that the powder will not be oxidized at 150-180°C, and ensure excellent conductivity. DETAILED DESCRIPTION
[0033] Testing and evaluation methods Determination of base metal conductive paste for stacking grid: Using the conductive paste of the embodiment or comparative example, Topcon paste is used as comparative example 1, HJT silver-copper paste is used as the conductive seed layer, and base metal conductive paste is used as the embodiment. Comparative example 1 is printed on a conventional BC screen (wet weight is controlled at 38-40 mg) and sintered at a conventional BC temperature with a peak temperature of more than 700°C; after sintering, the printed on the conventional screen is set aside for testing; the lower low-temperature HJT silver-copper paste seed layer (wet weight is controlled at 4-8 mg) is fully printed on the stacked grid screen, and after drying at 150°C for 1min, the upper conductive layer base metal paste of Examples 1-3 is continued to be printed respectively (wet weight is controlled at 32-34 mg), and placed for testing after curing at 180°C. Controlling the wet weight is to ensure that the metallized film layer, thickness, and width are as consistent as possible to improve the accuracy of the experiment.
[0034] Resistance test: Use a four-probe ohmmeter to test the resistance at both ends of the electrode.
[0035] Contact resistance: Prepare the samples to be tested as above; use a laser slicer to cut out battery cells of a specified size in the printed pattern area; use a TLM contact resistance device to measure the contact resistance.
[0036] Test the bonding strength between the stacked grid and seed layer: Use 3M tape, and then tear it apart.
[0037] The conductive seed layer silver-copper paste used in the following embodiment is a HJT conductive silver-copper paste, and the prepared paste includes, by mass percentage: 5.3% organic resin (45wt% bisphenol F epoxy resin, 25wt% hexahydrophthalic acid diglycidyl ester, 25% epoxy-modified acrylic resin, 5wt% trihydroxychloroacetic acid resin), 0.5wt% blocked hexamethylene diisocyanate trimer curing agent, 74.12wt% silver-copper powder (D50 is 3 μm, spherical), 18.88% silver powder (D50 is 0.5 μm, spherical), 0.2wt% isooctyl alcohol polyoxyethylene ether phosphate auxiliary agent, 1.0wt% solvent (the mass ratio of diethylene glycol butyl ether acetate, dimethyl malonate, and alcohol ester twelve is 6:3:1); The organic resin, curing agent, solvent and additive are mixed and then evenly mixed in a homogenizer at a speed of 600-1000 rpm; silver copper powder and silver powder are added to the obtained mixture and mixed at a speed of 600-1000 rpm; the mixed slurry is then ground by a three-roll mill until the slurry fineness reaches less than 5 μm, thereby obtaining HJT conductive silver copper slurry.
[0038] Bisphenol F epoxy resin, Shenzhen Jiadida New Materials Technology Co., Ltd., model NPEF-170; Bisphenol A epoxy resin, Nantong Xingchen Phoenix Synthetic Materials Co., Ltd., model WSR-618; Polyurethane resin, BASF Germany, model LR-9100; Ternary chloroacetic acid resin, Kunshan Pangao Chemical, model MVAH (hydroxyl), MVAM (carboxyl); Phenoxy resin, Mitsubishi Chemical, Japan, model JER-1256; Blocked hexamethylene diisocyanate trimer curing agent, Shanghai Sendi Chemical, model SD-120.
[0039] Example 1 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 80wt% micron-grade nickel powder (D50 3.2 μm, spherical), 12wt% nano-grade nickel powder (D50 0.2 μm, spherical); The antioxidant is: 25wt% of copper cyclohexaneate, 25wt% of triethanolamine, 25wt% of benzotriazole, 20wt% of coupling agent KH560, and 5wt% of dispersant BYK-111 are mixed together, manually stirred, and three-roll milled twice to prepare a composite antioxidant.
[0040] The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0041] Example 2 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 80wt% micron-grade copper powder (D50 3.5 μm, spherical), 12wt% nano-grade nickel powder (D50 0.2 μm, spherical); The antioxidant is: 25wt% of copper cyclohexaneate, 25wt% of triethanolamine, 25wt% of benzotriazole, 20wt% of coupling agent KH560, and 5wt% of dispersant BYK-111 are mixed together, manually stirred, and three-roll milled twice to prepare a composite antioxidant.
[0042] The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0043] Example 3 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 80wt% micron-grade copper powder (D50 3.5 μm, spherical), 12wt% nano-grade copper powder (D50 0.3 μm, spherical); The antioxidant is: 25wt% of copper cyclohexaneate, 25wt% of triethanolamine, 25wt% of benzotriazole, 20wt% of coupling agent KH560, and 5wt% of dispersant BYK-111 are mixed together, manually stirred, and three-roll milled twice to prepare a composite antioxidant.
[0044] The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0045] Comparative Example 1 Conventional BC high temperature sintering slurry on the market.
[0046] Comparative Example 2 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4.5wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.7wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 80wt% micron-grade copper powder (D50 3.5 μm, spherical), 12wt% nano-grade copper powder (D50 0.3 μm, spherical); The above-mentioned resin, curing agent, solvent and dispersant are added in sequence according to proportion, and after manual stirring, base metal powder is added, and after manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed, and the gap is from large to small, and the minimum gap must not be less than 10 μm; after grinding 6 times, canning; entering into a rotary mixer, stirring at 1000 rpm for 1 min, the preparation is completed.
[0047] Comparative Example 3 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4.5wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic acid resin), 1.7wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 80wt% micron-grade nickel powder (D50 3.2 μm, spherical), 12wt% nano-grade nickel powder (D50 0.2 μm, spherical); The above-mentioned resin, curing agent, solvent and dispersant are added in sequence according to proportion, and after manual stirring, base metal powder is added, and after manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed, and the gap is from large to small, and the minimum gap must not be less than 10 μm; after grinding 6 times, canning; entering into a rotary mixer, stirring at 1000 rpm for 1 min, the preparation is completed.
[0048] Comparative Example 4 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 92wt% micron-grade nickel powder (D50 3.2 μm, spherical); The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0049] Comparative Example 5 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 92wt% micron-grade copper powder (D50 3.5 μm, spherical); The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0050] Comparative Example 6 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyester resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 92wt% micron-grade copper powder (D50 3.5 μm, spherical); The above resin, curing agent, solvent and dispersant are added in sequence according to the proportion, and after manually stirring evenly, base metal powder is added, and after manually stirring until it is moistened and there is no dry powder, three-roll grinding is performed, and the gap is from large to small, and the minimum gap must not be less than 10 μm; after grinding 6 times, canning; entering into a rotary mixer, stirring at 1000 rpm for 1 min, the preparation is completed.
[0051] Comparative Example 7 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% acrylic resin, 5wt% trivalent carboxyl chloroacetic resin), 1.2wt% blocked hexamethylene diisocyanate trimer curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 92wt% micron-grade copper powder (D50 3.5 μm, spherical); The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0052] Comparative Example 8 A stacked gate conductive paste for a base metal layer, the composition and preparation method thereof are as follows: 4wt% resin (40wt% bisphenol F epoxy resin, 15wt% bisphenol A epoxy resin, 15wt% polyurethane resin, 25wt% phenoxy resin, 5wt% tricarboxylic chloroacetic resin), 1.2wt% 2-methylimidazole curing agent, 0.1wt% isooctyl alcohol polyoxyethylene ether phosphate dispersant, 1.7wt% solvent (35wt% N-methylpyrrolidone, 35wt% 1,6-hexanediol diglycidyl ether, 20wt% trimethylolpropane trimethacrylate, 10wt% glycerol), 1wt% antioxidant, 92wt% micron-grade copper powder (D50 3.5 μm, spherical); The above-mentioned resin, curing agent, solvent, dispersant and antioxidant are added in sequence according to proportion, and after manual stirring, base metal powder is added. After manual stirring until it is moistened and there is no dry powder, three-roll grinding is performed with the gap from large to small, and the minimum gap shall not be less than 10 μm; after grinding 6 times, canning is performed; the mixture is put into a rotary mixer at 1000 rpm and stirred for 1 min, and the preparation is completed.
[0053] Performance Testing: 1. Resistivity The results of the line resistivity test and the contact resistivity test of the products of the embodiment and the comparative example are shown in Table 1.
[0054] Table 1
[0055] According to the above invention, base metal powder can be appropriately selected and matched with the conductive adhesive composition of the present invention for metallization of heterojunction solar cells, thereby achieving the purpose of cost reduction.
[0056] In Comparative Examples 2 and 3, which are embodiments without adding antioxidants, the resistance is increased; in Comparative Examples 4 and 5, which do not add nano-copper powder and nano-grade nickel powder, the resistance is increased; in Comparative Examples 6 and 7, the resin is replaced, and the resistance is increased; in Comparative Example 8, the curing agent is replaced, and the resistance is increased.
[0057] 2. Bonding strength The embodiment and the comparative example were subjected to a 3M tape tearing test, and the test results are shown in Table 2 below.
[0058] Table 2
[0059] From the above content, it can be seen that the base metal powder is appropriately selected to be matched with the conductive adhesive composition involved in the present invention for use in heterojunction solar cell metallization, thereby achieving the purpose of cost reduction while realizing low resistance and good bonding strength.
[0060] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A conductive paste for a BC battery stacked grid base metal layer, characterized in that: The raw material composition is: (A) 92-93wt% base metal powder, (B) 3.8-4.2wt% resin, (C) 1.0-1.2wt% curing agent, (D) 1.2-2wt% solvent, (E) 0.3-0.8wt% additive, (F) 0.5-1wt% antioxidant; The antioxidant is a mixture of benzotriazole, triethanolamine, copper cyclohexaneate, a coupling agent and a dispersant.
2. The conductive paste according to claim 1, characterized in that The preparation method of the antioxidant is as follows: 20-25wt% of cyclohexane acid copper salt, 25-30wt% of triethanolamine, 15-25wt% of benzotriazole, 10-20wt% of silane coupling agent KH560 and 5-10wt% of dispersant BYK-111 are mixed, stirred, and three-roll milled twice to prepare the antioxidant.
3. The conductive paste according to claim 1, characterized in that: The base metal powder is one of copper powder, nickel powder, tin powder and aluminum powder or a mixture of two of them.
4. The conductive paste according to claim 1, characterized in that: The resin is one or more of epoxy resin, polyester resin, polyurethane resin, chloroacetic acid resin, phenoxy resin, polyimide resin and acrylic resin.
5. The conductive paste according to claim 1, characterized in that: The curing agent is one or more of blocked hexamethylene diisocyanate trimer, phthalic anhydride, methyltetrahydrophthalic anhydride and 2-methylimidazole.
6. The conductive paste according to claim 1, characterized in that: The solvent is one or more of DBE, alcohol ester dodecanedioate, dimethyl adipate, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, N-methyl pyrrolidone, 1,6-hexanediol diglycidyl ether, trimethylolpropane trimethacrylate, and glycerol.
7. The conductive paste according to claim 1, characterized in that: The auxiliary agent is one or more of a dispersant, a coupling agent, a hydroxy silicone oil, and a curing accelerator; the dispersant is one or more of oleic acid, polyethylene glycol, and isooctyl polyoxyethylene ether phosphate; the coupling agent is one or more of KH550, KH560, and KH570; the curing accelerator is one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, a boron trifluoride complex, dicyandiamide, and organic urea.
8. The method for preparing the conductive paste for the base metal layer of the BC battery stack as claimed in claim 1, characterized in that: The steps include: Add the required resin, curing agent, solvent, additive and antioxidant in proportion, stir evenly, add base metal powder, stir until moist and no dry powder, then grind with three rollers, with the gap from large to small, and the minimum gap must not be less than 10 μm; after grinding 6 times, pack into a can; put into a rotary mixer, 800-1000 rpm, stir for 1-2 min, and the preparation is complete.
9. A BC battery grid stack containing the conductive paste according to any one of claims 1 to 7, characterized in that: The BC battery stacked grid structure is divided into two layers, the lower layer is a conductive seed layer formed by HJT silver-copper paste, and the upper layer is a base metal layer containing the above conductive paste.
10. The BC battery stack according to claim 9, characterized in that: The silver content of the lower HJT silver copper paste is controlled at 25-30wt%; the paste of the conductive seed layer accounts for 10-20wt% of the entire grid line; the silver content of the upper conductive paste is 0%, and the paste accounts for 80-90wt% of the entire grid line; The upper and lower layers are cured at low temperature; the temperature is controlled at 150-180 ℃.
Citation Information
Patent Citations
Anti-oxidation conductive copper slurry as well as preparation method and application thereof
CN114005575A
Conductive copper paste, electrode and preparation method of conductive copper paste
CN115116650A
Low-temperature conductive paste, raw material composition thereof, heterojunction battery electrode and preparation method of heterojunction battery electrode
CN117936160A
Low-temperature curing type conductive silver paste, preparation method and application thereof
CN117976288A
IBC battery and preparation method thereof
CN118658922A
Cited By
TopCon back fine grid silver paste suitable for narrow-linewidth screen printing and preparation method of TopCon back fine grid silver paste
CN122067839A